Evaluasi Penggunaan Antibiotik pada Pasien Anak Infeksi Saluran Akut menggunakan Metode ATC/DDD - Fajriansyah; Akbar Awaluddin; Welly; Zulfahmidah (Postgraduate, University of Mataram, 2023)
The use of antibiotics needs to be monitored because it is known that excessive use of antibiotics can increase resistance in the community and this has become a focus both nationally and globally. This study aims to evaluate the use of antibiotics in patients with acute respiratory infection at Hasanuddin University Hospital using the ATC/ DDD analysis method. The research design used a cross-sectional study design with retrospective data collection. The sample in this study was patient medical record data from January-December 2021, taken from total sampling and met the inclusion and exclusion criteria. Descriptive statistics are used to present and analyze data. Evaluation of the use of antibiotics by quantitative methods ATC/DDD (Anatomical Therapeutic Chemical (ATC)/Defined Daily Dose (DDD), DDD/1000/ patient/day. The results showed that the most widely used antibiotic was ampicillin (280 mg) 32.96 DDD/1000 patients/day and the lowest was cefadroxil (150 mg) 1.45 DDD/1000 patients/day. Antibiotics with the highest DDD / 100-patient days value and exceeding the WHO DDD standard were ampicillin antibiotics from the penicillin group with a DDD / 100 patient-day value of 32.96 DDD /100 patient-days.